Atomski laser - Venturini, Rok (Matrika, 2016)
In this article I describe an atom laser, which is analogous to an optical laser, but instead of electromagnetic radiation, an atom laser emits coherent matter waves. After a brief introduction to optical lasers, I describe the BoseEinstein condensate and its experimental realization using laser cooling methods. Then, I describe the experimental setup of an atom laser with Bose-Einstein condensate as an active medium and compare the properties of optical and atom laser. Finally, I describe the application of the atom laser in atom interferometry.
Keywords: atom interferometry; atom laser; atomska interferometrija; atomski laser; Bose-Einstein condensate; Bose-Einsteinov kondenzat; optical laser; optični laser